Studi Komparasi Antara Pendapat Madzhab Maliki dan Madzhab Syafi’i tentang Mahar Mitsil Bagi Istri yang Ditinggal Mati Suaminya Qobla Dukhul - Yayat Dimyati (Sekolah Tinggi Agama Islam At-Tahdzib, Ngoro, Jombang, Indonesia, 2019)
One of the issues that need to be highlighted as well as the attention among Muslims is the issue of dowry, especially in the situation of a husband who does not determine the dowry and dies qabla dukhul. Furthermore, regarding the dowry of qabla dukhul, there were differences of opinion from several Muslim scholars, especially Maliki and the Shafi'i School of Religion. The purpose of this study was to find out the opinions of Madhab Maliki and Syafi'i Madhhab about the dowry of the night for the wife left behind by her husband qobla dukhul and to find out about the law of Madhab Maliki and Syafi'i Madhhab to find out the similarities and differences of opinion between the two schools. The results showed that according to the Maliki School of Wife whose wife had left her husband qobla dukhul and had not mentioned the dowry, the wife was not entitled to receive dowry but was entitled to inheritance. Whereas according to the Shafi'i School of Religion in this matter, it was argued that if the wife left behind by her husband qobla dukhul while the husband did not mention the dowry, the wife would still be entitled to receive dowry and inheritance. Based on the analysis in this study, it can be concluded that the differences of opinion between the Maliki Madrasah and the Syafi'i Madhhabis are caused by the conflict between qiyas and atsar. Madhab Maliki stressed the dowry of prices on buying and selling. So when the husband dies qobla dukhul, the husband does not need to pay dowry. The Maliki school of thought took up the argument by referring to the friend of Ali ibn Abi Talib. While the Shafi'i School of Understanding has an understanding that when the marriage contract has taken place, and the marriage becomes legal from the side of the law, the bride price must be given to the wife. This opinion holds to the hadith narrated by Tirmidhi from Ibn Mas'ud